2003
DOI: 10.1902/jop.2003.74.9.1282
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Regeneration in Humans Using Recombinant Human Platelet‐ Derived Growth Factor‐BB (rhPDGF‐BB) and Allogenic Bone

Abstract: Use of purified rhPDGF-BB mixed with bone allograft results in robust periodontal regeneration in both Class II furcations and interproximal intrabony defects. This is the first report of periodontal regeneration demonstrated histologically in human Class II furcation defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
285
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(306 citation statements)
references
References 23 publications
(28 reference statements)
9
285
0
4
Order By: Relevance
“…Using doses similar to those used in this study, rhPDGF-BB enhanced periodontal bone repair in rats and humans. [37][38][39] In addition, rhPDGF-BB treatment at doses used in this study significantly enhanced fracture healing in aged, osteopenic rats. 40 Fracture callus cell proliferation was significantly higher in the diabetic rats treated with rhPDGF-BB, indicating that rhPDGF-BB treatment can ameliorate the deficit in callus cell proliferation observed in diabetic animals ( Figs.…”
Section: Fracture Healing In a Diabetic Rat Modelmentioning
confidence: 89%
“…Using doses similar to those used in this study, rhPDGF-BB enhanced periodontal bone repair in rats and humans. [37][38][39] In addition, rhPDGF-BB treatment at doses used in this study significantly enhanced fracture healing in aged, osteopenic rats. 40 Fracture callus cell proliferation was significantly higher in the diabetic rats treated with rhPDGF-BB, indicating that rhPDGF-BB treatment can ameliorate the deficit in callus cell proliferation observed in diabetic animals ( Figs.…”
Section: Fracture Healing In a Diabetic Rat Modelmentioning
confidence: 89%
“…Geriatric and osteoporotic patients may have a different biological potential for wound healing than nongeriatric, nonosteoporotic patients based on preclinical studies suggesting a reduction in lineage progression and proliferative activity of osteoblast progenitor cells and gene expression, a decrease in osteoblast function, diminished osteoblast response to signaling cues, and an imbalance between the coupling of bone formation and resorption. 2,[4][5][6][7][8]11,22,29,30 Therefore, the biological properties of rhPDGF-BB may be an important therapeutic consideration for geriatric and osteoporotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…20 In human patients with advanced periodontal lesions, rhPDGF-BB combined with allograft bone matrix stimulated alveolar bone formation. [21][22][23] Furthermore, local application of rhPDGF-BB at doses of 1.0 and 0.3 mg/ml with a beta-tricalcium phosphate (b-TCP) carrier in human clinical studies significantly enhanced bone formation 24 which was maintained for 2 years following treatment. 25 Therefore, based upon the demonstrated success of rhPDGF-BB to stimulate new bone formation in both animal models and in human clinical studies, 1.0 and 0.3 mg/ml rhPDGF-BB concentrations were selected and combined with b-TCP and collagen and tested in an osteoporotic rat fracture model.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several techniques used in modern clinical dentistry emerged from the application of tissue engineering principles. The use of growth factors and platelet concentrates are an example of how such approaches are present and growing in dentistry 15,[21][22] . The use of PRP was the first generation of blood concentrates to be used with the aim of improving bone repair in surgeries 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In order to extract only stem cells, it is necessary for culture media suitable for such cells to be used in both techniques. Although enzymatic digestion is a faster isolation method, studies have shown that the use of on growth factors 21 . Moreover, the literature presents just one case of the application of growth factors in root canal revascularization 22 .…”
Section: Bioactive Moleculesmentioning
confidence: 99%